Rattus tanezumi ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Rattus tanezumi (Temminck, 1844) — Oriental House Rat Mus tanezumi Temminck in Siebold, Temminck, and Schlegel, 1844 p.51; Type locality- Nagasaki (restricted by Jones & Johnson, 1965), Japan. Rattus rattus alexandrinus: Kishida & Mori, 1931 p.378; Kuroda, 1938 p.65. R. rattus rattus: Kishida & Mori, 1931 p.378; Won, 1968 p.176. Rattus norvegicus longicaudus Mori, 1937 p.42; Type locality- Ulleung (Dagelet) Island, Korea; Won, 1958 p.449; Won, 1968 p.176. R. tanezumi: Kuroda, 1938 p.69; Musser & Carleton, 2005 p.1489; Kim et al., 2013 p.550. R. rattus flavipectus: Ellerman, 1949 p.58; Jones & Johnson, 1965 p.390. R. rattus: Ellerman & Morrison-Scott, 1951 p.581; Won, 1958 p.448; Won, 1968 p.176; Yoon, 1992 p.82; Han, 1994 p.47; Won & Smith, 1999 p.28; Han, 2004c p.119; Jo et al., 2012 p.253. R. alexandrinus: Won, 1958 p.448. R. rattus rufescens: Won, 1967 p.236. Range: The range of R. tanezumi converges in the central and southern regions of Korea, with populations especially ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 184, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...